During the second and third wave of the COVID-19 pandemic, the dynamics of the spread of disease in our region: a study based on hospital data - Güliz Evik; Gamze Gelici; Sümeyye Aksu; Mustafa Serhat Şahinoğlu; Gülden Ersöz (Romanian Journal of Infectious Diseases)
Aim. The SARS-CoV-2 Omicron variant became predominant in Turkey in January 2022, coinciding with a rise in SARS-CoV-2–associated hospitalizations. Material and methods. Patients diagnosed with COVID-19 were collected by the infection control committee through an active surveillance program for COVID-19 throughout the pandemic. The hospitalization rate was included in the model to evaluate the relationship between each wave period and disease severity. The basic demographic data of the patients, and the potential risk factors such as comorbid diseases, and laboratory findings were included in the analysis. Results. The rate of patients who were positive in August (26.8%) was found to be significantly lower than in February (45.9%) (p <.001). The proportion of inpatient patients treatment in August (2.3%) was found to be significantly higher than in February (1.2%) (p <.001). In addition, in the omicron variant patients' wave, the neutrophil/lymphocyte ratio was 5.31, and it was observed to be significantly higher than that of the patients (Median = 3.95) in the delta variant wave (p=.023). Discussion. These results provide clinicians with information about the clinical course of COVID-19 patients and are very important for appropriate clinical decision-making in these patients. It is critical to continue to update COVID-19 management protocols based on the latest research.